Changes in plant species composition and functional traits along the successional trajectory of a restored patch of Atlantic Forest - Suganuma, M. S.; Assis, G. B. de [UNESP]; Durigan, G. (Akademiai Kiado, 2014)
Studies on the dynamics of ecosystems undergoing restoration are needed to verify whether they are following the expected trajectory, developing in unexpected ways, or becoming stabilized in a non desirable intermediate stage of blocked succession. In order to elucidate the successional trajectory of the plant community in a 20 ha patch of riparian Atlantic Forest (southeastern Brazil) undergoing restoration, we assessed native tree and shrub species regenerating at 18, 28 and 38 years after planting. We analyzed changes in floristic composition and proportions of functional traits, by comparison with the set of 166 species originally planted most of which were non-native, and with the plant assemblages of two reference riparian ecosystems - a primary-type and a secondary forest, in the same eco-region. Despite isolation from extant forests, immigrating native species have enriched and dominated the community undergoing restoration. Thus, the floristic composition and the proportions of species among functional guilds is becoming more distinct through time from the set of species planted and more similar to the nearest secondary forest (1.6 km), but is still dramatically different from that of a primary forest 50 km away. The proportions of functional guilds among individuals regenerating have shown stability over time but differ in general from the primary forest, particularly for the higher proportion of zoochorous plants in the forest undergoing restoration. The proportion of non-native species as well as of individuals of these species in the community have decreased over time, even though they were the majority of the species planted, refuting the hypothesis of priority effect driving the community assembly.
Keywords: Assembly rules; Community dynamics; Natural regeneration; Reference ecosystem; Tropical riparian forest